GAMIFICATION IN LANGUAGE LEARNING: SUPPORTING STUDENTS WITH SPECIAL NEEDS IN ENGLISH ACQUISITION - Ergasheva Ozodabonu Bahodirjon qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article explores the role of gamification in enhancing English language learning for students with special needs. It discusses the benefits, challenges, and practical strategies of using game-based learning to support language acquisition in diverse learners. The study highlights how gamification can improve motivation, engagement, and learning outcomes.